Genomic fingerprinting of Borrelia burgdorferi sensu lato by pulsed-field gel electrophoresis. - Belfaiza, J (1993)
A total of 46 Borrelia burgdorferi sensu lato isolates that were isolated from patients with Lyme borreliosis and infected animals or were extracted from ticks of the genus Ixodes were analyzed. Large restriction fragment patterns obtained after cleavage of genomic DNAs with MluI were analyzed by pulsed-field gel electrophoresis (PFGE). To eliminate the contribution of plasmid DNA, only fragments greater than 70 kb were used for the analysis. The results indicated that each of the 14 B. burgdorferi sensu stricto isolates were recognized by a band at 135 kbp, each of the 12 Borrelia garinii isolates by two bands (220 and 80 kbp), and each of the 20 Borrelia afzelii isolates by three bands (460, 320, and 90 kbp). Whereas differences in the PFGE patterns among B. burgdorferi sensu stricto isolates and B. garinii isolates were noted, B. afzelii isolates were all similar. Identification of isolates by PFGE correlates with their belonging to a given species within B. burgdorferi sensu lato.